2019
DOI: 10.1021/acs.iecr.9b00104
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Process Simulation Using OpenModelica

Abstract: The equation-oriented general-purpose simulator OpenModelica provides a convenient, extendible modeling environment, with capabilities such as an easy switch from steady-state to dynamic simulations. This work reports the creation of a library of steady-state models of unit operations using OpenModelica. The use of this library is demonstrated through a few representative flowsheets, and the results are compared with the steady-state simulators Aspen Plus and DWSIM. Being open-source and supported by a large c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The project was released in 2007 but abandoned in 2011; it was difficult to continue given a lack of a development roadmap and its use of Python v2.2 (which is no longer supported). OMChemSim is a recently published software written in Open Modelica and is focused on modeling unit operations and mass and energy balances. A key gap, however, is that algorithms for the rigorous design of unit operations as well as economic analyses are not included yet.…”
Section: Introductionmentioning
confidence: 99%
“…The project was released in 2007 but abandoned in 2011; it was difficult to continue given a lack of a development roadmap and its use of Python v2.2 (which is no longer supported). OMChemSim is a recently published software written in Open Modelica and is focused on modeling unit operations and mass and energy balances. A key gap, however, is that algorithms for the rigorous design of unit operations as well as economic analyses are not included yet.…”
Section: Introductionmentioning
confidence: 99%
“…This enhances the applicability of the software for a wide range of processes, including bioprocesses. Several studies have reported the application and comparison of DWSIM with other process modeling softwares for chemical processes [15,16]. More recently, Elavazhagan et al [17] have reported the application of DWSIM for the simulation of biodiesel production by transesterification.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the performance of the two tools was similar, although some details were lacking in order to make a thorough assessment. Nayak et al [18] compared results obtained with DWSIM, Aspen Plus and a property package implementation in OpenModelica. A few examples involving distillation of water/methanol, ethylene glycol production including distillation of water and glycol/ethylene oxide as well as a conversion reactor (ethanol to ethyl acetate) are shown.…”
Section: Introductionmentioning
confidence: 99%